KERAGAMAN GENETIK JAHE (Zingiber officinale Roscoe) MENGGUNAKAN TEKNIK PENANDA MOLEKULER Random Amplified Polymorphic DNA (RAPD) - Choirul Rizka Putri; Hermin Pancasakti Kusumaningrum; Endang Kusdiyantini (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Ginger plant in Indonesia is known there are three kinds of varieties, namely red ginger, emprit ginger and big ginger. Ginger (Zingiber officinale Roscoe) is one of the medicinal plants that could potentially be produced in increasing quantities and wide distribution in Indonesia that may affect patterns of genetic diversity. This study aims to determine patterns of genetic diversity of three varieties of ginger (red ginger, big ginger and emprit ginger) obtained from BALITRO, Bogor and BPTP, Ungaran using two primers (OPA1 and OPA2). Techniques of molecular markers RAPD (Random Amplified Polymorphic DNA) is one of the techniques used for the analysis of genetic diversity. The study begins by isolating DNA from 30 samples of ginger leaves, then amplification with primers OPA1 and OPA2 which then results of electrophoresis converted into the form of binary data and phylogenetic tree construction with 2:02 NYTSYS program. The results obtained are worth a total of 20 polymorphic band (86.9%) and 3 pita monomorphic (13%) with primary OPA1 and OPA2. Heterozygosity values in a row is worth 0.9026 and 0.889. Distance genetic similarities in this sample has the highest value is 1 and the lowest is 0.3. The relationship between the three varieties of big ginger are distant relationship with red ginger and emprit ginger. Red ginger and emprit ginger still have a close genetic relationship. Key Word : Genetic Diversity, Zingiber officinale, RAPD